2022
DOI: 10.1088/1402-4896/ac9866
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of GaN/quartz nanostructure using pulsed laser ablation in liquid

Abstract: The pulsed laser ablation approach was used to synthesize gallium nitride (GaN) nanoparticles (NPs) at six distinct ablation energies. The nanoparticle was deposited on a quartz substrate using the drop cast technique. Two peaks of h-GaN nanostructures are detected in the XRD pattern, at 2θ = 34.64 and 37.98, reflected from the (002) and (100) planes, respectively. The hexagonal crystal nature of GaN is indicated by the morphological features, which is shown in the XRD pattern. The greatest laser power, 2000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…XRD identification of the core–shell configuration 119 121 showed that these results are in line with the study 122 . When exposed to X-ray radiation, the greater concentrations of aggregated silver nanoparticles resulted in a greater degree of reflection 123 , 124 . For the WO 3 sample, two peaks appeared at 2θ: 28.92° and 58.84°.…”
Section: Resultsmentioning
confidence: 99%
“…XRD identification of the core–shell configuration 119 121 showed that these results are in line with the study 122 . When exposed to X-ray radiation, the greater concentrations of aggregated silver nanoparticles resulted in a greater degree of reflection 123 , 124 . For the WO 3 sample, two peaks appeared at 2θ: 28.92° and 58.84°.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 (a,b,c) illustrated the transmission, absorption and the energy gap of the grown In2O3 thin film over the quartz substrate at different laser energies ranging from 1200 mJ -2000 mJ [42][43][44]. As the laser energy increase the transmission decrease while the absorption increased due to the increased of the deposition rate which leads to increase the thin film thickness, the highest transmission observed at 1200 mJ with the lowest absorption [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…The target is mounted on the platform; it spins to avoid colliding in the same place, and to ensure the best removal, the laser impacts the target at a 45-degree angle. [42][43][44].…”
Section: Gan Films Are Prepared By Pldmentioning
confidence: 99%